Improving Student Mathematics Understanding through Problem-Based Learning - Putri, Cut Septiya; Anwar; Usman, (International Journal of Scientific Research and Management (IJSRM), 2020)
This study aimed to improve students’ mathematics understanding through Problem-Based Learning. The subjects were Year 8 students in one of the junior high schools in Sigli, Indonesia. The main instrument used in this study was a mathematical understanding test, while the supporting instrument was the observation sheets of student and teacher activities. The data were analyzed qualitatively and described descriptively. The results showed that students' mathematics understanding reached the classical mastery learning of 62.50% and 75.00% for the cycle I and II, respectively. Based on these results, it can be concluded that the ability of mathematics understanding enhanced through the Problem-Based and Learning model. Keywords: Problem-Based Learning, Mathematics Understanding, Junior High Schools.